Livelihood Resiliency of Selected Informal Sectors in Cebu City, the Philippines - Esguerra, James G.; Jardin, Roselle A.; Tayco, Ryan O. (Human Behavior, Development and Society, 2024)
This study focused on the livelihood resiliency of selected informal sectors in Cebu City, the Philippines. It employed a mixed-method approach to describe how informal sectors responded to external shocks. A quantitative approach was used to measure three resilience capacities: absorptive, adaptive, and transformative resilience. The results revealed that both street and platform vendors showed high resilience capacities. When relationships between gender and resilience capacity levels were tested for street and platform vendors, only gender and adaptive capacities showed significant relationships at the .02 and .04 levels, respectively. By contrast, their absorptive and transformative resilience capacities showed no significant differences. Qualitative findings revealed that informal sector street and platform vendors were vulnerable in times of economic shock due to their irregular incomes, poor working conditions, and struggles to sell their products. Despite external shocks, they attempted to cope by looking for alternative sources of income, utilizing their savings, and receiving assistance from the government, along with support from their families.